2009
DOI: 10.3390/molecules14114396
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl-3-octylimidazolium Chloride—Sorption and Primary Biodegradation Analysis in Activated Sewage Sludge

Abstract: Ionic liquids (ILs) are known to be non-volatile and thus to have low potential for atmospheric contamination or intoxication of humans by inhalation. However ILs have the potential to contaminate soil and water as they might be water soluble and can be sorbed onto solids. The investigation of possible natural ways of reducing the concentration of ILs in the environment is of high importance, especially because the requirement for biodegradable chemicals increases, together with pressure for reduction of incin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
(25 reference statements)
1
32
0
Order By: Relevance
“…The lack of adsorption is explained by the fact that the electrostatic and hydrophobic attractive forces are not suffi cient to absorb the tested ionic liquid under given conditions (Gorman-Lewis & Fein 2004). The activated sludge is a more complex adsorbent, therefore the study of adsorption on this material may give different results, what was confi rmed by Markiewicz et al (2009). They described an adsorption process of 1-methyl-3--octylimidazolium chloride [Omim][Cl] onto activated sludge and have found a high level of sorption of tested IL.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The lack of adsorption is explained by the fact that the electrostatic and hydrophobic attractive forces are not suffi cient to absorb the tested ionic liquid under given conditions (Gorman-Lewis & Fein 2004). The activated sludge is a more complex adsorbent, therefore the study of adsorption on this material may give different results, what was confi rmed by Markiewicz et al (2009). They described an adsorption process of 1-methyl-3--octylimidazolium chloride [Omim][Cl] onto activated sludge and have found a high level of sorption of tested IL.…”
Section: Introductionmentioning
confidence: 82%
“…They described an adsorption process of 1-methyl-3--octylimidazolium chloride [Omim][Cl] onto activated sludge and have found a high level of sorption of tested IL. This result shows that sorption plays a signifi cant role in the removal of xenobiotics from wastewater (Markiewicz et al 2009). …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…1). Liwarska-Bizukojc (2011) also reported the inhibitory effect of 1-alkyl-3-methylimidazolium bromides on the activity of dehydrogenases in activated sludge biomass, which increased with the increase in the chain length of the alkyl substituent, whereas Markiewicz et al (2009) estimated that at 1-methyl-3-octylimidazolium chloride of concentration higher than 0.2 mM, the activity of dehydrogenases in the cells dropped markedly. Also Azimova et al (2009) measured the effect of imidazolium-derived ionic liquids on the bacterial respiration rate.…”
Section: Resultsmentioning
confidence: 99%
“…Markiewicz et al showed that a level of 0.2mM 1-methyl-3-octylimidazolium chloride is the terminal concentration threshold for primary biodegradation. Higher concentrations led to sorption onto the sewage sludge flocs, although inhibition of cell function as a consequence of decreased dehydrogenase activity was observed (Markiewicz et al, 2009). This indicates that the toxicity of ILs towards activated-sludge microorganisms should be taken into consideration.…”
Section: Biological Methodsmentioning
confidence: 99%